Saudi Society of Emergency Medicine, 7th Scientific Assembly - Saudi Society of Emergency Medicine (Saudi Journal of Emergency Medicine)
Saudi Society of Emergency Medicine, 7th Scientific Assembly 2022 - ABSTRACTS [SJEMed 2022; 3(3.100): S1-S22]